MENINGKATKAN HASIL BELAJAR SISWA KELAS III TERHADAP MATA PELAJARAN PKN PADA TOPIK KEWAJIBAN DAN HAK MELALUI PENERAPAN METODE TEAM GAMES TOURNAMENT (TGT) DI SDIT AL MADINAH KABUPATEN MAROS TAHUN 2023 - Rismayanti; Isfahani, Rizki; Susilowati, Yuni (Jurnal Nusantara Madani, 2023)
Background: The research was conducted by a teacher with the aim of improving the quality of learning for pupils. This was done in response to the low average learning outcomes of students of grade III at SDIT Al Madinah district of Maros, where only about 33% of the 24 pupils achieved grades in PKn subjects. Subject and Methods: Classroom Action Research (CAR) is conducted at SDIT Al Madinah in Maros district using class III C as a research subject, consisting of 24 pupils. The research consists of three cycles and each cycle has four stages: 1) Planning, 2) Implementation, 3) Observation, and 4) Reflection. Results: From data analysis, both qualitative and quantitative descriptive, it was revealed that before the application of the Team Games Tournament (TGT) method, the average student learning score was 67,09. However, after the implementation of the TGT method, there was a significant improvement so that the average learning score reached 71,67. In the first cycle, as many as 19 pupils have achieved the learning level, while the other 5 pupils have not reached it. In the second cycle the average learning performance of pupils has increased to 79.58 and the total of 24 students have reached the score of competence, achieving 100% success. Conclusion: Using the learning method Team Games Tournament (TGT) has improved pupils' learning results in PKn subjects in the third grade of SDIT Al Madinah district of Maros. Keywords: Pupil learning outcomes; Learning points; Team Games Tournament methods (TGT)